2017
DOI: 10.1007/s11920-017-0802-x
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia as a Precipitating Factor in New Onset Mental Illness: a Systematic Review of Recent Findings

Abstract: A literature yielded 1859 unique articles meeting search criteria were identified; 16 articles met all selection criteria and reviewed with some studies reporting on more than one mental health outcome. Overall, the review supports the hypothesis that insomnia is a predictor of subsequent mental illness. The evidence is strongest for an insomnia-depression relationship. The new studies identified and reviewed add to a modest number of publications supporting a prospective role of insomnia in new onset mental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
126
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(130 citation statements)
references
References 79 publications
2
126
0
2
Order By: Relevance
“…Controlled trials demonstrated improvements in chronic migraine frequency following behavioral sleep treatment. The treatment group did exhibit a decrease in nighttime awakenings but all headache endpoints were equal to placebo, including [76][77][78] Insomnia and/or daytime sleepiness are symptoms of mood and anxiety disorders as well as chemical dependencies. Using a rigorous statistical approach and pooling evidence from the 2 controlled trials that each employed 1.5 hours of therapist contact (either one 90-minute 71 or three 30-minute treatment sessions 70 ), Smitherman and colleagues determined headache frequency was reduced at 6-8 week follow-up in the behavioral sleep treatment group 6.2 fewer headache days per month than the sham control group.…”
Section: Assess Sleep Disturbance and Insomnia In Chronicmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled trials demonstrated improvements in chronic migraine frequency following behavioral sleep treatment. The treatment group did exhibit a decrease in nighttime awakenings but all headache endpoints were equal to placebo, including [76][77][78] Insomnia and/or daytime sleepiness are symptoms of mood and anxiety disorders as well as chemical dependencies. Using a rigorous statistical approach and pooling evidence from the 2 controlled trials that each employed 1.5 hours of therapist contact (either one 90-minute 71 or three 30-minute treatment sessions 70 ), Smitherman and colleagues determined headache frequency was reduced at 6-8 week follow-up in the behavioral sleep treatment group 6.2 fewer headache days per month than the sham control group.…”
Section: Assess Sleep Disturbance and Insomnia In Chronicmentioning
confidence: 99%
“…Psychiatric Comorbidity.-Psychiatric disorders are comorbid with both headache 74,75 and sleep disorders. [76][77][78] Insomnia and/or daytime sleepiness are symptoms of mood and anxiety disorders as well as chemical dependencies. 61 Screening may be warranted especially when either insomnia or hypersomnia is present.…”
Section: Assess Sleep Disturbance and Insomnia In Chronicmentioning
confidence: 99%
“…The importance of recognizing insomnia as a problem in its own right has been highlighted in the DSM‐5 recommendation that ‘insomnia disorder’ should be coded ‘whenever diagnostic criteria are met whether or not there is a co‐existing physical, mental or sleep disorder’ (American Psychiatric Association, ). In addition, mounting evidence suggests that chronic insomnia constitutes a risk factor for the development of physical and mental health problems (Khan and Aouad, ; Pigeon et al ., ). Similarly, insomnia is predictive of work disability (Sivertsen et al ., ), poorer quality of life (Kyle et al ., ) and higher societal costs (Leger and Bayon, ).…”
Section: Introductionmentioning
confidence: 97%
“…It is positively related to mood disorder severity, cognitive dysfunctions, levels of hopelessness, increased risk of substance abuse, aggressive and impulsive behaviours, emotional dysregulation and increased risk of suicidality (Baglioni, Spiegelhalder, Lombardo, & Riemann, 2010;Ritter et al, 2011;Boudebesse & Henry, 2012;Ritter et al, 2012;Conroy & Arnedt, 2014;Kamphuis, Dijk, Spreen, & Lancel, 2014;Schaffer et al, 2015;Kanady, Soehner, Klein, & Harvey, 2017;Ng et al, 2015;Woosley, Lichstein, Taylor, Riedel, & Bush, 2014;Woznica, Carney, Kuo, & Moss, 2015). Insomnia plays an important role in relapses and recurrences of mood disorders, it is an independent risk factor for mood disorders, and a frequent early sign occurring prior to both depressive and manic episodes (Baglioni et al, 2011;Ellis, Perlis, Gardani, Bastien, & Espie, 2014;Gruber et al, 2011;Kanady, Soehnera, & Harvey, 2015;Pigeon, Bishop, & Krueger, 2017;Ritter et al, 2015;Rumble et al, 2015;Sakurai, Suzuki, Yoshimura, Mimura, & Uchida, 2017). Recently, it has been shown that targeting insomnia may improve not only insomnia symptoms but favourably impacts on the trajectory of mood disorders (Franzen & Buysse, 2008;Geoffroy et al, 2017;Jansson-Fröjmark & Norell-Clarke, 2016;Manber et al, 2011) and, by reducing depressive symptoms, it may even prevent major depressive forms (Christensen et al, 2016).…”
mentioning
confidence: 99%